2022
DOI: 10.1186/s12934-022-01961-8
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of l-malic acid production from acetate with Aspergillus oryzae DSM 1863 using a pH-coupled feeding strategy

Abstract: Background Malic acid, a dicarboxylic acid mainly used in the food industry, is currently produced from fossil resources. The utilization of low-cost substrates derived from biomass could render microbial processes economic. Such feedstocks, like lignocellulosic hydrolysates or condensates of fast pyrolysis, can contain high concentrations of acetic acid. Acetate is a suitable substrate for l-malic acid production with the filamentous fungus Aspergillus oryzae DSM 1863, but concentrations obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…Arginine dihydrolase (ADH) can convert arginine to ornithine, accompanied by the release of carbon dioxide and ammonia, as well as playing a crucial role in nitrogen storage and remobilization [22]. Malic acid (MTE) is a dicarboxylic acid mainly used in the food industry and can be produced by microbial fermentation oxidation/ reduction TCA and glyoxylic acid pathways, as well as from fossil resources [23]. By shaker fermentation, lactose is effectively converted to lactose acid (LAC), which is widely used in the pharmaceutical, food, nanotechnology and chemical industries [24].…”
Section: Discussionmentioning
confidence: 99%
“…Arginine dihydrolase (ADH) can convert arginine to ornithine, accompanied by the release of carbon dioxide and ammonia, as well as playing a crucial role in nitrogen storage and remobilization [22]. Malic acid (MTE) is a dicarboxylic acid mainly used in the food industry and can be produced by microbial fermentation oxidation/ reduction TCA and glyoxylic acid pathways, as well as from fossil resources [23]. By shaker fermentation, lactose is effectively converted to lactose acid (LAC), which is widely used in the pharmaceutical, food, nanotechnology and chemical industries [24].…”
Section: Discussionmentioning
confidence: 99%
“…When grown in shaking flasks on acetate, A. oryzae yielded up to 21% g L -malate /g acetate but the production was highly dependent upon the initial acetate concentration [ 64 ]. In bioreactor experiments optimized for L-malate production from acetate, A. oryzae produced about 29 g/L L-malate corresponding to a 29% g L -malate /g acetate L-malate yield [ 63 ]. During the cultivation of A. oryzae with acetate and acetol from a detoxified PAC, L-malate was produced up to 7.3 ± 0.3 g/L (corresponding to a yield of 20 ± 0.01 g L -malate /g substrates ) [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fungi have been reported to be the microorganisms most tolerant to the oil fraction of the condensates from pyrolysis [56], and the tolerance of Aspergillus oryzae to PAC and some selected PAC components has been characterized before [48,57,58]. A. oryzae is known for its metabolic versatility to grow on sugars and carboxylic acids present in various waste streams for the production of single cell proteins [59][60][61][62] or L-malate [63][64][65], among other chemicals. L-Malate has a wide array of applications, ranging from taste-enhancer in the food industry to biopolymer production [66].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that ADH was found in ArgZ from Synechocystis and AgrE from Anabaena , which play crucial roles in nitrogen storage and remobilization [ 31 ]. Malic acid, a dicarboxylic acid mainly used in the food industry, can be produced by microbial fermentation via oxidation/reduction of TCA and glyoxylic acid pathways, and can also be produced from fossil resources [ 32 ]. Lactococcus lactis biovar diacetylactis is one of the main strains that degrade citrate in dairy product starter cultures.…”
Section: Discussionmentioning
confidence: 99%